2012
DOI: 10.1038/hdy.2012.21
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining genetic diversity and population panmixia through dispersal and not gene flow in a holocyclic heteroecious aphid species

Abstract: Heteroecious holocyclic aphids exhibit both sexual and asexual reproduction and alternate among primary and secondary hosts. Most of these aphids can feed on several related hosts, and invasions to new habitats may limit the number of suitable hosts. For example, the aphid specialist Aphis glycines survives only on the primary host buckthorn (Rhamnus spp.) and the secondary host soybean (Glycine max) in North America where it is invasive. Owing to this specialization and sparse primary host distribution, host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
55
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 55 publications
6
55
2
Order By: Relevance
“…Soybean aphids migrate from soybean to Rhamnus in early autumn, where they sexually reproduce, admixing avirulence and virulence in the next generation. Though this movement has not been studied in detail, it is likely to mirror the movement of soybean aphid from Rhamnus to soybean, i.e., being characterized by local migration with strong bottlenecks (Bahlai et al 2010, Orantes et al 2012. Local migration by soybean aphid suggests that populations in the northern United States and southern Canada would have the greatest genetic input to the following generation, as Rhamnus species distribution is asymmetric with the greatest density in these regions (Heimpel et al 2010).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Soybean aphids migrate from soybean to Rhamnus in early autumn, where they sexually reproduce, admixing avirulence and virulence in the next generation. Though this movement has not been studied in detail, it is likely to mirror the movement of soybean aphid from Rhamnus to soybean, i.e., being characterized by local migration with strong bottlenecks (Bahlai et al 2010, Orantes et al 2012. Local migration by soybean aphid suggests that populations in the northern United States and southern Canada would have the greatest genetic input to the following generation, as Rhamnus species distribution is asymmetric with the greatest density in these regions (Heimpel et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…A regionally based IRM plan for Rag varieties may be most effective under these conditions. However, the soybean aphid rapidly disperses over large distances (Orantes et al 2012), and even aphids from distant Þelds may still be involved in sexual reproduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because both primary and secondary hosts are common and soybean aphids disperse extensively among them on an annual basis, there are few barriers to gene flow among soybean aphid populations, resulting in genetic homogenization across North America (Orantes et al, 2012). Because both primary and secondary hosts are common and soybean aphids disperse extensively among them on an annual basis, there are few barriers to gene flow among soybean aphid populations, resulting in genetic homogenization across North America (Orantes et al, 2012).…”
Section: Geographic Distribution and Intrabiotypic Variability Of Foumentioning
confidence: 99%
“…Because both primary and secondary hosts are common and soybean aphids disperse extensively among them on an annual basis, there are few barriers to gene flow among soybean aphid populations, resulting in genetic homogenization across North America (Orantes et al, 2012). Orantes et al (2012) and Wenger and Michel (2013) concluded that late-season aphid dispersal homogenizes the aphid population and increases genetic diversity before colonization of buckthorn, the primary host. They concluded that these patterns are consistent with expected biotypic virulence due to either nongenetic (possibly environmental) mechanisms or widely dispersed genetic mechanisms.…”
Section: Geographic Distribution and Intrabiotypic Variability Of Foumentioning
confidence: 99%